Assessing reliability and validity of the Child PTSD Symptom Scale in portuguese adolescents - Pinto, Ricardo José Martins (2022)
Objective This study assessed psychometric properties of a self-reported measure of posttraumatic stress disorder (PTSD) for adolescents based on DSM-5 criteria–the Child PTSD Symptom Scale–Self Report. We tested the internal consistency, test-retest reliability, and convergent validity. Method The participants were 317 Portuguese adolescents (53% females) between 13 and 17 years old who had experienced at least one traumatic event or one childhood adversity. A subset of the sample (n = 85) completed test-retest measures (interval range between 5 and 7 months). Results Analyses revealed good to excellent internal consistencies, moderate to good agreement test-retest reliability, and good convergent validity. Conclusions Results supported the use of the CPSS-SR-5 scale as a valid and reliable measure for the identification of PTSD symptoms and probable diagnosis according to DSM-5 criteria in Portuguese adolescents.